Structure and Dynamics of Granular Materials Perturbed by External Fields - Gerasymov, O.I. (Український фізичний журнал, 2010)
The problem of the description of a local structure of granular materials is discussed within the concept of existence of structural invariants. The superimposition of this approach with the probabilistic arguments concerning the crossover to the kinetics of a transition between states with different measures gives a relevant picture of the evolution with a reminiscence of the first-order phase transition between states with different structural orderings.